Cell-Free DNA as a Diagnostic and Prognostic Biomarker in Dogs With Tumors - Kim, Jihu; Bae, Hyeona; Ahn, Soomin; Shin, Sunwoo; Cho, ARom; Cho, Kyu-Woan; Jung, Dong-In; Yu, DoHyeon (Frontiers in Veterinary Science, 2021)
Cell-free DNA (cfDNA) is derived from apoptosis/necrosis, active cellular secretion, and lysis of circulating cancer cells or micrometastases. In humans, cfDNA is widely used in cancer diagnosis, but veterinary research has yet to be actively conducted to establish it as a cancer biomarker. This retrospective study analyzed cfDNA levels in samples collected from dogs with neoplastic disease (n = 38), clinically ill dogs without neoplasia (n = 47), and healthy dogs (n = 35). cfDNA levels and clinical data were compared among groups, and prognostic analyses were performed within the neoplastic group. Furthermore, continual cfDNA measurements were performed during the chemotherapy of six dogs with lymphoma. Dogs with neoplasia showed significantly higher cfDNA concentrations than dogs without neoplasm, and the cfDNA concentration in the lymphoid neoplasia group was significantly elevated among all neoplastic groups. Dogs with neoplasia and a plasma cfDNA concentration above 1,247.5 µg/L had shorter survival rates than those with levels below this threshold (26.5% versus 86.1%, respectively, P < 0.05). In cases with complete remission in response to chemotherapy, the cfDNA concentration was significantly decreased compared to the first visit, whereas the cfDNA concentration was increased in cases with disease progression or death. Interestingly, a significant correlation was found between lymph node diameter and cfDNA concentration in dogs with multicentric lymphoma (R2 = 0.26, P < 0.01). These data suggest that changes in cfDNA concentration could be used as a diagnostic biomarker for canine neoplasia. Furthermore, increased plasma DNA levels might be associated with shorter survival time, and cfDNA concentrations may reflect the response to chemotherapy.